Sustainable Historic Districts: Vitality Analysis and Optimization Based on Space Syntax - Jian-Ming Fu; Yi-Fan Tang; Yu-Kai Zeng; Li-Yi Feng; Zhi-Gang Wu (Buildings)
As modern society increasingly emphasizes quality of life, historic districts face the challenge of balancing the preservation of traditional culture with the integration of urban development. Many historic districts today struggle with low vitality and limited visitor engagement. By adopting sustainable development strategies, such as promoting tourism, these districts have the potential to enhance economic vitality. This study explores the spatial morphological characteristics of the ShuiXiLin Historic District (SHD) in Fuzhou, using spatial syntax theory and tools within the framework of sustainable urban renewal. The study proposes three strategies for the district: (1) enhancing connectivity positively influences the public experience within the SHD; (2) strengthening the district’s primary axis amplifies its influence across the area; (3) implementing protective reuse of historical buildings and improving service facilities can significantly enhance the district’s vitality. Through theoretical analysis and a review of existing research, this study proposes revitalization strategies aimed at formulating sustainable development plans for the district. These recommendations are intended to offer valuable insights for urban renewal projects and provide theoretical support for planning decisions related to the vitality of historic districts. This research illustrates the effective use of spatial syntax in historic districts, offering a robust method to evaluate and enhance the spatial structure and vitality of heritage areas. It supports sustainable development by integrating preservation with modern needs, ensuring a balance between conservation and urban growth.